The effect of combined AC electric field and ultrasound on the chemical compositions and Escherichia coli content of spearmint aromatic water. (23rd November 2017) - Behruzian, Ava; Hosseinzadeh Samani, Bahram; Rostami, Sajad; Lorigooini, Zahra; Behruzian, Mehrsa
Abstract: The aromatic waters are one of the forms of the use of medicinal plants, mostly for edible or medicinal uses. They are required to control the microbial load. Common methods of pasteurization by reason of applying high temperatures cause the undesirable changes in taste, odor, medicinal properties, nutritional quality, and reduction in essential oil. Therefore, novel methods of pasteurization have been widely used recently. In order to determine the microbial inactivation by pulsed electric field and ultrasound, Escherichia coli at a concentration of 7 × 10 6 /mL was inoculated to spearmint aromatic water. The field intensities of 5, 7.5, and 10 kV/cm with time durations of 5, 20, and 35 s and ultrasound powers of 100, 150, and 200 W with time durations of 3, 4, and 5 min were applied. The data obtained from the experiments were analyzed using response surface methods. The results showed that the effect of the four variables listed on the inactivation of microorganisms and energy consumption per cycle of microbial reduction are significant. At the end, the process was optimized. The optimum values for the electric field intensity, time of applying the field, the ultrasound power, and sonication time were 10 kV/cm, 35 μs, 185.90 W, and 4.47 min, respectively. It should be noted that the proposed method had minimal changes in the chemical composition of the raw spearmint aromatic water and was superior to conventional heating methods. Practical applications: The mint aromatic water is used in food, pharmaceutical, and personal care industries; it is necessary to microbiological control of its content. Because of conventional pasteurization methods cause undesirable changes in taste, smell, and nutritional quality with a reduction in the amount of essential oil. For this purpose, researchers are looking for solutions that by combining new thermal and nonthermal approaches, the damaging effects of conventional pasteurization be removed. However, the main challenge facing the nonthermal technologies in food processing is the inactivation of pathogenic microorganisms and food spoilage agents, which can be achieved by various methods. The aim of the present research was examined the simultaneous effect of the ultrasonic and the electric field to remove microorganism and save quality and benefit chemical compositions of medicinal aromatic water. This research introduces an innovative and combined method for aromatic water pasteurization and this method can benefit to the food industry.